2008
DOI: 10.2147/jpr.s4324
|View full text |Cite
|
Sign up to set email alerts
|

Problems and barriers of pain management in the emergency department: Are we ever going to get better?

Abstract: Pain is the most common reason people visit emergency rooms. Pain does not discriminate on the basis of gender, race or age. The state of pain management in the emergency department (ED) is disturbing. ED physicians often do not provide adequate analgesia to their patients, do not meet patients' expectations in treating their pain, and struggle to change their practice regarding analgesia. A review of multiple publications has identifi ed the following causes of poor management of painful conditions in the ED:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The gender distribution was the same, the mean age was similar in our study and the mean pain intensity was similar [3] [6] [7] [8]. Our data are inferior to those of Guéant S et al [9] who Open Journal of Emergency Medicine…”
Section: Discussionsupporting
confidence: 53%
“…The gender distribution was the same, the mean age was similar in our study and the mean pain intensity was similar [3] [6] [7] [8]. Our data are inferior to those of Guéant S et al [9] who Open Journal of Emergency Medicine…”
Section: Discussionsupporting
confidence: 53%
“…Although this review focused on contemporary studies to reflect contemporary practice, the tools cited are quite dated and may not be relevant to current clinical practice and settings when compared with their development forty years ago. Factors such as patient knowledge via internet, patient expectation, along with new medications and changes to clinical management, influence current care delivery in the ED (Motov & Khan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 gives a brief about the potential causes and biases of Oligoanalgesia in an emergency setting. 6 In an emergency setting, it is the onus of the healthcare professional to assess and manage the patients' symptoms appropriately. Hence it becomes paramount that the healthcare practitioner should consider all the factors mentioned in above table, both patient and doctor-related, when treating any patient in the emergency setting.…”
Section: Causes Of Oligoanalgesia In Emergency Settingsmentioning
confidence: 99%
“…Potential factors for Oligoanalgesia in an emergency setting: 6,7. Pain is assumed to be an expected byproduct of trauma and ignored Management of other symptoms take priority over pain management Studies over the years have shown that only 60% of patients received analgesics with delays up to 90 min.…”
mentioning
confidence: 99%